Effects of pursed-lip breathing and forward trunk lean postures on total and compartmental lung volumes and ventilation in patients with mild to moderate chronic obstructive pulmonary disease: An observational study. Issue 51 (18th December 2020) - Ubolnuar, Nutsupa; Tantisuwat, Anong; Thaveeratitham, Premtip; Lertmaharit, Somrat; Kruapanich, Chathipat; Chimpalee, Jaturong; Mathiyakom, Witaya
Abstract : Abstract: This study identified the effects of pursed-lip breathing (PLB), forward trunk lean posture (FTLP), and combined PLB and FTLP on total and compartmental lung volumes, and ventilation in patients with chronic obstructive pulmonary disease (COPD). Sixteen patients with mild to moderate COPD performed 2 breathing patterns of quiet breathing (QB) and PLB during FTLP and upright posture (UP). The total and compartmental lung volumes and ventilation of these 4 tasks (QB-UP, PLB-UP, QB-FTLP, PLB-FTLP) were evaluated using optoelectronic plethysmography. Two-way repeated measures ANOVA was used to identify the effect of PLB, FTLP, and combined strategies on total and compartmental lung volumes and ventilation. End-expiratory lung volume of ribcage compartment was significantly lower in PLB-UP than QB-UP and those with FTLP ( P  < .05). End-inspiratory lung volume (EILV) and end-inspiratory lung volume of ribcage compartment were significantly greater during PLB-FTLP and PLB-UP than those of QB ( P  < .05). PLB significantly and positively changed end-expiratory lung volume of abdominal compartment (EELVAB ) end-expiratory lung volume, EILVAB, tidal volume of pulmonary ribcage, tidal volume of abdomen, and ventilation than QB ( P  < .05). UP significantly increased tidal volume of pulmonary ribcage, tidal volume of abdomen, and ventilation and decreased EELVAB, end-expiratory lung volume, and EILVAB than FTLP ( P  < .05). In conclusion, combined PLB with UP or FTLP demonstrates a positive change in total and compartmental lung volumes in patients with mild to moderate COPD.